Digital Inequality: The Internet in Mauritius - Gopee, Shafiiq Muhammad (Curtin University, 2016)
The research explores the existence of and factors relating to the experience of Digital Inequality in the context of a small island developing state, Mauritius. It investigates the dimensions of Digital Inequality and its socio-economic determinants among Mauritian Internet users. This is achieved through a combination of analysis of existing literature, a survey of users, and interviews with key local Internet stakeholders. The outcome provides a holistic insight into these phenomena in such milieu.